Tribological capabilities of chiral nematic liquid crystal additives in mineral motor oil - Vadim Mokshin (Advances in Mechanical Engineering, 2020)
This article presents the results of experimental investigation of tribological properties of commercial mineral motor oil with chiral nematic (also known as twisted nematic or cholesteric) liquid crystal additives. Cholesteryl stearate and valerate (fatty acid cholesterol esters) liquid crystals were used as oil additives in investigation. Tribological experiments were performed using a block-on-disc-type tribo-test machine at constant experiment time and sliding velocity conditions. The load (contact pressure), concentration of liquid crystalline additive in oil and Rz roughness of steel–steel friction surfaces were taken as variable parameters. The mean coefficient of friction of steel–steel friction pair lubricated by oil with and without liquid crystal additives and near-contact temperature were taken as dependent variables. Regression equations were then derived for each lubricant and tribological efficiency of liquid crystals as oil additives was evaluated. It was established that coefficient of friction of steel–steel friction pair and near-contact temperature are reduced to about a half in the presence of liquid crystal additives. Results of tribological experiments show that tribological efficiency of liquid crystals as oil additives increases with increase in their molecular mass.